Time for curriculum reform: the case of mathematics. Issue 4 (1st December 2013) - Noyes, Andrew; Wake, Geoff; Drake, Pat
Abstract : Mathematics education is rarely out of the policy spotlight in England. Over the last 10 years, considerable attention has been given to improving 14–19 mathematics curriculum pathways. In this paper we consider some of the challenges of enacting curriculum change by drawing upon evidence from our evaluation of the Mathematics Pathways Project (MPP). From 2004 to 2010 this project, which was directed by England%s Qualifications and Curriculum Authority, aimed to improve the engagement, attainment and participation rates of 14‐ to 19‐year‐old learners of mathematics. Our particular focus is upon the temporal problems of piloting new curriculum and assessment and we draw on Lemke%s discussion of timescales, heterochrony and the adiabatic principle to consider the interlocking and interference of various change processes.